ANALISIS PEMBANGKIT LISTRIK TENAGA ANGIN DI DESA SUNGAI NIBUNG KECAMATAN TELUK PAKEDAI KABUPATEN KUBU RAYA - Syamsul Bahari . (Faculty of Engineering, Universitas Tanjungpura, 2015)
ABSRACT - West Borneo province is very broad and many the villages have not gotten the electricity. Energy sources used to to generate electricity up to now is still dominated by fossil fuels. The wind is renewable energy source and environmently friendly that has the potential to replace fossil fuels and that potential is widely available in the west Borneo. This thesis discussed about analysis the wind power plant which is located in the Sungai Nibung village especially for house of worship ( mosque ) and patrol post. The methods used in the completion of this thesis is assisted by Homer Software to determine the feasibility of building a wind power plant in the village with Electric Generator (generator) with a capacity equal to the wind turbin as a comparison which will see the number of NPC (Net Present Cost ) and the lowest COE (Cost Of Energy). Based on the simulation results of two power plant that is the wind power plant and the generator ( generator ) with 500 watts capacity obtained the NPC for wind turbins 3.857 ( Rp 48.212,5 ) , coe 0.314 / kwh ( Rp 3.925 / kwh ) and for genarator electricity ( generator ) the npc 6.003 (Rp 75.037,5 ) , coe 0.489 / kwh ( Rp 6.112,5 / kwh ). Meanwhile for electricity generating 1000 Watt capacity for Wind Turbin NPC obtained for 5,386 (Rp 67 325), coe 0.439 / kwh ( Rp 5.487,5 / kwh ) and for an electric generator ( generator ) the value of the npc 9.758 ( rp 121.975 ) , coe 0.795 / kwh ( rp 9.937,5 / kwh ). In accordance with the data peak load of 285 watts, therefore the wind power plant with 500 watts capacity is appropriate to develop in the Sungai Nibung village. Key words: Analysis The Wind Power Plant, Homer Software Simulation.